Tratamiento de aguas residuales provenientes de la industria (2013)
ABSTRACT: In the present study, the electrochemical degradation of textile dye indigo carmine (IC) was performed using dimensionally stable anodes (DSA) of Ti/IrO2-SnO2 doped with Sb2O5. The effect of different salts (NaCl, Na2SO4 and NaHCO3) used as supporting electrolyte was analyzed. The results showed that the oxidation dye IC is enhanced when NaCl is present in the solution due to the action of oxidizing species HClO/ClO- electro generated from the conductive medium. In the presence of NaCl, it was achieved a rapid removal of color and chemical oxygen demand. The results show the great potential of applying this technology to the treatment of wastewater from the textile industry.